Maternal Characteristics and Feeding Practices and Its Relationships with the Incidence of Toddlers Stunting in Dompu, West Nusa Tenggara, Indonesia - Raisa Namira; Ahmad Syauqy; Ani Margawati; Diana Nur Afifah (Universitas Diponegoro, 2026)
This research aims to determine the relationship of maternal characteristics and feeding practices on the stunting incidence in toddlers. It was conducted using a retrospective observational method with a case-control design. A quantitative and qualitative approach was also implemented. The population used was toddlers aged 1-3 years in West Dompu Public Health Center. Furthermore, purposive sampling was used to select the 46 respondents in each group. Data were collected using questionnaires, in-depth interviews, and observations. Meanwhile, the analysis was conducted through the univariate, bivariate, multivariate, and qualitative methods. The results of the qualitative analysis showed that the eating habits of some of the toddlers could lead to stunting. These habits were the consumption of less diverse food types, intake of food that do not meet nutritional standards, and the belief in certain foods. Inappropriate parenting and irregular eating patterns were also found to increase the incidence of stunting. However, inadequate energy was the most dominant causative factor.